2023
DOI: 10.3389/fpls.2023.1138184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungus inoculation on the growth and nitrogen metabolism of Catalpa bungei C.A.Mey. under different nitrogen levels

Abstract: Evidence suggests that arbuscular mycorrhizal fungi (AMF) may promote the growth of woody plants. However, the effects of AMF on nitrogen (N) metabolism in plants, especially trees, and its regulatory mechanism are rarely reported. Here, the effects of AMF inoculation on the growth and N nutrition status of Catalpa bungei under different N levels were reported. Three N levels (low, medium, high) and two mycorrhizal inoculation treatments (inoculation with Rhizophagus intraradices or not) were used with factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, highstrength (3/4 and full-strength) exogenous EE-GRSP treatments dramatically reduced the contents of glucose, total amino acids, and flavonoids in the tea leaves, which may be related to the eutrophication in the rhizosphere of tea plants caused by exogenous GRSP application. Generally, excessive organic or inorganic content in the soil may reduce the decomposition and release of proteases by the roots, thereby inhibiting the absorption and utilization of nutrients, such as nitrogen, by plant roots [29,30]. Therefore, we speculate that, in the present study, high-strength exogenous EE-GRSP application resulted in eutrophication of the tea rhizosphere soil, thereby decreasing nutrient absorption and utilization, as well as the transport efficiency of the tea roots.…”
Section: Discussionmentioning
confidence: 64%
“…Meanwhile, highstrength (3/4 and full-strength) exogenous EE-GRSP treatments dramatically reduced the contents of glucose, total amino acids, and flavonoids in the tea leaves, which may be related to the eutrophication in the rhizosphere of tea plants caused by exogenous GRSP application. Generally, excessive organic or inorganic content in the soil may reduce the decomposition and release of proteases by the roots, thereby inhibiting the absorption and utilization of nutrients, such as nitrogen, by plant roots [29,30]. Therefore, we speculate that, in the present study, high-strength exogenous EE-GRSP application resulted in eutrophication of the tea rhizosphere soil, thereby decreasing nutrient absorption and utilization, as well as the transport efficiency of the tea roots.…”
Section: Discussionmentioning
confidence: 64%
“…Evaluating the effect of the combined application of AMF and PGPR revealed that the mixture of both microbial substrates enhanced rice plants' nutritional content and yield. In addition to that, the consortium of AMF and PGPR significantly enhanced the levels of inorganic nutrients like boron (B), N, P, and K in rice field soils, thus providing the plants with sufficient nutrients for proper growth and yield (Chen et al 2023a). Similarly, inoculation of AMF and PGPR consortium on date palms undergoing Fusarium wilt decreased the disease incidences.…”
Section: Association Of Amf With Other Microbes For Enhancing the Eff...mentioning
confidence: 99%
“…Additionally, exogenous EE-GRSP applications did not significantly affect the root N content, but high-strength EE-GRSP applications dramatically decreased the leaf N content, and it is possible that GRSP only maintained the plants’ N at its required stable level. After all, excessive N concentrations would inhibit plant growth [ 38 ].…”
Section: Discussionmentioning
confidence: 99%